1992
DOI: 10.1017/s0001566000002385
|View full text |Cite
|
Sign up to set email alerts
|

Intrapair Differences of Physical Aging and Longevity in Identical Twins

Abstract: The genetic and environmental contributions to physical aging (hair graying, balding, presbyopia) and longevity (age at death) were examined by within-pair comparison in monozygotic (MZ) and dizygotic (DZ) twins in later adulthood. Physical aging was investigated on 135 pairs of adult twins aged over 50. Hair graying and hair loss (baldness) showed significantly higher rates of concordance in the MZ twins than in the DZ twins. The intrapair difference of the degree of hair graying was negligible in 79%, slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Twin or adoption studies may be used to separate genetic and environmental effects and to investigate the strength of these effects. During the recent decades, registers mainly in the Nordic countries have made large twin studies possible [Hayakawa et al, 1992;McGue et al, 1993;Herskind et al, 1996;Iachine et al, 1998]. A twin study, based on registers from Denmark, Sweden, and Finland in which the resemblance in mortality among pairs of monozygotic twins and pairs of dizygotic twins was compared, supports the fact that there is a genetic influence on mortality [Iachine et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Twin or adoption studies may be used to separate genetic and environmental effects and to investigate the strength of these effects. During the recent decades, registers mainly in the Nordic countries have made large twin studies possible [Hayakawa et al, 1992;McGue et al, 1993;Herskind et al, 1996;Iachine et al, 1998]. A twin study, based on registers from Denmark, Sweden, and Finland in which the resemblance in mortality among pairs of monozygotic twins and pairs of dizygotic twins was compared, supports the fact that there is a genetic influence on mortality [Iachine et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…This seemed surprising, since studies on the degree of hair loss among monozygotic twins aged over 50 have shown that intrapair differences were negligible in 92%, slight in 8% and striking in none [1]. A salient feature differing the two brothers in their personal histories was that the balding brother admitted to heavy cigarette smoking, while the other was a non-smoker.…”
Section: Introductionmentioning
confidence: 99%
“…Twin-or adoption studies may be used to separate genetic and environmental effects and to investigate the strength of these effects. During recent decades, registers mainly in the Nordic countries have made large twin studies possible [Hayakawa et al, 1992;McGue et al, 1993;Herskind et al, 1996;Iachine et al, 1998]. A twin study, based on registers from Denmark, Sweden, and Finland in which the resemblance in mortality among pairs of monozygotic twins and pairs of dizygotic twins was compared, supports that there is a genetic influence on mortality [Iachine et al, 1998;Christensen and Vaupel, 1996].…”
Section: Introductionmentioning
confidence: 99%